LAPORAN KEUANGAN SEBAGAI ALAT PENGAMBILAN KEPUTUSAN BAGI UMKM UNTUK MAJU - Harsono, Yhonanda; Widodo, Adji; Saprudin, Udin (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
The purpose of this community service is to provide counseling to MSMEs who are partners of Bakmi Jowo in Ruko Komplek Vila Dago, Pamulang, South Tangerang. This is very important for MSMEs so that they can pay attention to making financial reports properly and correctly. Participants in this community service consisted of Pamulang University lecturers, Management Study Program as resource persons, employees and owners of Bakmi Jowo, and invited 4 MSME players who were partners of Bakmi Jowo. The method used is to conduct presentations, discussions, and questions and answers to MSMEs about the scope of their business, followed by a workshop on how to make financial reports. Recording financial statements is one of the important things in the continuity of a company, both large companies and small businesses (MSMEs). Every company must have good and correct financial reports according to accounting standards, this aims to determine the condition and financial performance of the company and can help company owners in making decisions. This event aims to assist MSMEs in preparing financial reports based on SAK EMKM. Observations were made that there were four MSME participants, namely Bakmi Jowo, Ayam Geprek Asli, Harjuna Catering and Tyas Kraft. Of the four MSMEs, all have made financial records, only most of them are not in accordance with existing financial standards. It is hoped that in the future they will do what the service team directs, be it daily journals, profit and loss statements and balance sheets, so that the development and position of their business assets can be monitored.